Challenges Associated with Formal Education in Rural Areas - Flynn, Paul; Mujčinović, Alen; Ferreira, Tatiana; Bojnec, Štefan; Neagu, Gabriela; Unay-gailhard, Ilkay; Rocca, Antonella; Lendzhova, Vladislava; Mamuchevska, Daniela (COST - CA18213, 2022)
The youth demographic in rural areas continues to experience a global decline despite significant efforts from both national and international organisations to downturn this negative trend. Such efforts aim to create conditions for learning as well as opportunities that can enable young people to develop knowledge, skills, and competencies. Despite the economic recovery trends of recent years (before the COVID-19 pandemic), young people continue to be particularly vulnerable and especially during times of crisis. Youth disengagement from the labour market can lead to economic loss, demotivation, marginalisation, and be reflected in challenges such as a lack of qualifications, health issues, poverty, and other forms of social exclusion. To address such challenges, it is vital that a detailed understanding of youth needs is developed. This work should be based on heterogeneous characteristics (personal vs institutional) that include (although not limited to) socio-economic, demographic, financial, technical, and institutional perspectives. This information should subsequently inform both future policy-making and decision-making processes. Previous research has already identified some problems related to the rural (suburban) regions. Common findings include: higher travel; communication and training costs; costly or inadequate services; lack of quality teachers; limited educational, training, social and economic opportunities; and an abundance of social capital. Such conditions clearly have an impact on youth development, where: • The share of young people aged 15-29 neither in employment nor in education or training (NEETs) are significantly higher, for example, in rural areas (in Europe, in 2019 12.6% of youth NEETs aged 15-29); • The rate of male early leavers tends to be higher than women (12% for men, and 8,1% for women) and where there is a higher incidence of early leavers among young people in rural areas (10.5%) and suburbs (11.2%) compared to those in cities (8.7%); • More females tend to enrol in general education programmes. Also, in rural areas within the youth population, those progressing to higher education that are aged 30 to 34 is only 29.4% despite a target of 40% set up by the EU Strategy compared to urban youth where this rate is 51.6%; • Internet connections and usage of the internet increases this is hampered by the rate of availability and adoption of digital equipment in rural areas. In addition, 33% of 13 to 14 years old did not have a high proficiency level in digital competencies, with 20% of young people aged 16 to 24 in the EU lacking basic digital skills. In order to address the aforementioned and other issues associated with youth development, a new form of partnership based on trust, collaborative working relationships between schools, sports clubs, art centres, museums, health centres need to be established and promoted. A common goal is required that seeks to maintain thriving rural communities, reduce segregation, improve the quality of life in rural areas, and transform regions towards a more sustainable one. This new form of partnership and process of developing new rural policies is based on creating an enabling environment through the (i) connection of markets, social networks, and information, (ii) civic, political participation, skills and (iii) education and empowerment, and general productivity. This Policy Brief takes a closer look at the issues raised above and makes a number of recommendations that can inform the development of the Youth-Centred Rural Transition Model (Figure 1) as a consequence of helping to shape policy and empower decision making that will make a difference to the everyday lives of Rural NEETs.
Keywords: Rural NEETs, school-to-work transition, unemployment, youth policy